Ghana. - Dept., International Monetary Fund. African (IMF Staff Country Reports., 2015)
EXECUTIVE SUMMARY Context. The emergence of large fiscal and external imbalances in recent years, which led to a slowdown in growth, is putting Ghana's medium-term prospects at risk. The Government's efforts to achieve fiscal consolidation since mid-2013 have been undermined by policy slippages, external shocks and rising interest cost. Until mid- 2014, the net international reserves position had further weakened and the exchange rate depreciated sharply, fueling inflationary pressures. The situation has stabilized on the back of the Eurobond issued in September and a short-term loan contracte.